Parenting: Strategi mendidik anak dalam era digital di Desa Karanganyar - Febrisyam, Adam Abiyu; Safira, Niken Marta; Elsania, Nilna; Guhir, Ahmad Gorang Khatami (Maliki Interdisciplinary Journal, 2024)
In the era of globalization and technological advancements, parents in Karanganyar Village face challenges in educating their children amidst the digital wave. This article describes the situation in Karanganyar Village, outlines relevant educational strategies considering local values, and optimizes the positive potential of technology. The implementation of parenting in the digital era in Karanganyar Village involves building digital awareness with children, providing well-structured access to technology, utilizing technology for learning, maintaining a balance between online and offline activities, and reinforcing local values in the digital context.